Holy Quranic Manuscripts: Examining Historical Variants and Transmission Methods - Salman Faris TC (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
. This research delves into the captivating realm of Holy Quranic manuscripts, embarking on a comprehensive exploration of their historical variants and transmission methods. The study encompasses an in-depth analysis of the revelation, compilation, and preservation of the Holy Quran, tracing its journey from inception to contemporary times. The primary objectives are to elucidate the historical evolution of Quranic manuscripts, analyze transmission methods, investigate the existence of textual variants, and assess the significance of these variants for understanding the Quran's development. Employing a meticulous interdisciplinary approach, this study synthesizes textual analysis, historical research, and comparative analysis to scrutinize early manuscripts, assess their characteristics, and trace the transmission routes. Advanced digital tools complement traditional scholarship to unravel intricate details. The research reveals the dynamic interplay between socio-historical contexts and manuscript transmission, shedding light on how the Quran's textual variations reflect evolving linguistic norms and theological interpretations. This investigation underscores the importance of preserving and comparing diverse manuscripts to enrich our understanding of Islamic history and spirituality.